HUBUNGAN SELF EFFICACY DAN SELF MANAGEMENT DENGAN KUALITAS HIDUP PASIEN DIABETES MELITUS TIPE II DI WILAYAH KERJA PUSKESMAS LEMBURSITU KOTA SUKABUMI - Septia Nurbayanti, Mega; Saeful Alamsyah, Mustopa; Abdillah, Hadi (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
Diabetes mellitus is a group of metabolic conditions that manifest as hyperglycemia and are characterized by abnormalities in insulin secretion. Improper management of diabetes can result in various complications that can even lead to death. This affects the patient's quality of life. The application of self-management of diabetes mellitus patients is influenced by various factors, one of which is self-efficacy. This study aims to determine the relationship between self-efficacy and self-management with the quality of life of type 2 diabetes mellitus patients in the work area of the overtime health center in Sukabumi City.This study uses quantitative research. The research method used is the Descriptive Correlational method with a cross sectional approach, using a simple random sampling technique of probality sampling type with a total sample of 64 respondents and analyzed using the Chi-Square testThe results showed that self-efficay patients were in the less category (71.9%), patient self-management was in the less category (56.3%) and the quality of life of type 2 diabetes mellitus patients in the work area of the overtime health center is in the sufficient category (67.2%). Based on the results of the chi-square test, a P value was obtained: 0.001 0.05, where it can be concluded that there is a relationship between self-efficacy and the quality of life of type 2 diabetes mellitus patients in the Overtime Health Center Working Area, Sukabumi City, and from the Chi-Square test results, a P value of 0.000 0.05 was obtained, where it can be concluded that there is a relationship between self-management and the quality of life of type 2 diabetes mellitus patients in the work area of the overtime health center, SukabumiPasien City. it is advisable to remain confident and optimistic in living a good future, always be open-minded and involve the family in the problems or circumstances at hand, and lifestyle changes, do good and regular check-ups and be more obedient to the care or treatment that is being carried out. so as to maintain and improve the quality of life.